Melioidosis: the great mimicker presenting as spondylodiscitis. (8th February 2018) - Garg, Rahul; Shaw, Tushar; Bhat, Shyamasunder N; Mukhopadhyay, Chiranjay
Abstract : Melioidosis, a syndrome with protean clinical manifestations, is caused by Gram-negative soil saprophyte Burkholderiapseudomallei . Among its diverse clinical presentations, the involvement of spine is a rare phenomenon and can mimic tuberculosis on presentation. A 65-year-old female with a known case of diabetes presented with fever with lower back pain. Blood culture grew Staphylococcus aureus, and as per sensitivity report, clindamycin and cefazolin were started. X-ray and MRI lumbosacral spine showed spondylodiscitis (likely Koch's). Decompression and biopsy were done, and a sample was sent for microbiological investigations that showed no growth of any significant pathogen; furthermore, all tests for tuberculosis diagnosis also remained negative. Active Melioidosis Detect Lateral Flow Assay was used on the tissue sample, which was positive for B. pseudomallei Capsular Polysaccharide (CPS) antigen; the case was confirmed by typethree secretion system 1 PCR for melioidosis. Antibiotics were changed to parenteral ceftazidime for 2 weeks followed by oral cotrimoxazole. A dedicated team of microbiologists and physicians is required to identify and treat the disease.